Faithful Father: The Case of the Traveling Priest - Pollock, Kathy S.; Papiernik, Janet C. (Journal of Leadership, Accountability and Ethics, 2017)
This case describes Father Rodney Rodis’ 14-year fraud while serving as pastor of two Roman Catholic rural parishes in central Virginia. Fr. Rodis, who suffered from chronic health issues, was indicted on mail fraud and money laundering in federal court and on 10 different felony counts in a state court case. He was ordered to pay back almost 600,000 to the Catholic Diocese of Richmond and sentenced to eighteen years in prison. Although Fr. Rodis’ congregations were devastated by the fraud, more troubling was the disloyalty by their beloved priest. Fr. Rodis was also a husband and father.